THE DYNAMICS OF CULTURAL LIFE IN NEW UZBEKISTAN - Zulayho Tilavova (Bright Mind Publishing, 2025)
This article presents concise reflections on the dynamic processes occurring under the conditions of New Uzbekistan, specifically regarding the ongoing efforts to construct a contemporary cultural identity of the country.
Keywords: Cultural life, cultural environment, dynamics of cultural development, culture of New Uzbekistan, cultural identity of the country.